The “new space” of homo digitalis: Questioning humans in the digital age - Dasion, Agustinus Gergorius Raja; Prananta, Arie Wahyu (Digital Theory, Culture & Society, 2024)
This study aims to address two main theses. First, this study focuses on the question of how technology and digitalization create people who cannot be separated from technology, called homo digitalis. Second, this study seeks to open a discourse of “new space” that is different from the real space created by homo digitalis. By using the method of literature review, this study is expected to lay the foundation for scientific studies on digitalization and the formation of new spaces in the era of digital technology. The results of the study refer to two basic arguments. First, homo digitalis is not just a user of technology. He exists through and in digital machines. That is, he exists in the confinement and governmentality of digital technology. Second, the new space created by homo digitalis is very different from real space. This does not mean that the new space is notreal, but the new space is considered real even though it is telepresent. This study is the basis for redefining space and human existence in the digital world.